The effectiveness of the discovery and the expository approaches in the teaching of social studies in a rural high school - Caballero, Victorina Liongson 1950- (1976)
The author attempted to find out evidences that would show the effectiveness of the discovery and expository approaches in the teaching of social studies in a rural high school.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Social sciences -- Study and teaching (Secondary) -- Sta. Maria, Bulacan; Learning by discovery